1993
DOI: 10.1590/s0101-81751993000300009
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da densidade populacional sobre as curvas de crescimento de Macrobrachium rosenbergii (De Man) em cultivo semi-intensivo (Crustacea, Palaemonidae)

Abstract: . TH E EFFECT OF STOCKING DENSITY ON MACROBRACHIUM ROSENBERG II (D E MAN) GROWTH CURVES lN EARTHEN PONDS (CRUSTACEA, PALAEMONIDAE). ln this artic\e the length growth curves of Macrobrachium rosenbergii (De Man, 1879) held in different population densities were analysed. Postlarvae prawns were stocked into five 0,02 ha earthen ponds at densities of 4, 8, 12, 16 and 20 ind./m 2 during six months. Forthnightly, the mean total length of animaIs from each pond were obtained by means of random samples. For each pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 14 publications
3
6
0
3
Order By: Relevance
“…This behavior may be considered a protection and escape strategy which enables M. brasiliense to survive predation in its natural habitat. Macrobrachium prawns are known to have individual aggression (Valenti et al 1993), and when they occur in high densities, larger males occupy the substrates where sheltering is easier, while smaller males occupy the other substrates where they are generally more exposed (Ling 1969, Peeble 1979a,b, Cohen et al 1981, Valenti et al 1993. In our study, we showed that adult individuals of M. brasiliense, from the smallest to the largest individuals, choose the same substrate.…”
Section: Discussionsupporting
confidence: 54%
“…This behavior may be considered a protection and escape strategy which enables M. brasiliense to survive predation in its natural habitat. Macrobrachium prawns are known to have individual aggression (Valenti et al 1993), and when they occur in high densities, larger males occupy the substrates where sheltering is easier, while smaller males occupy the other substrates where they are generally more exposed (Ling 1969, Peeble 1979a,b, Cohen et al 1981, Valenti et al 1993. In our study, we showed that adult individuals of M. brasiliense, from the smallest to the largest individuals, choose the same substrate.…”
Section: Discussionsupporting
confidence: 54%
“…The same was observed with the average weight of each morphotype (Cohen et al 1981; Karplus et al 1986; D’Abramo et al 1989; Siddiqui et al 1997). The results of the present study shows that the density effect is markedly stronger when the variation occurs at lower levels in M. amazonicum ; the same occurs in M. rosenbergii (Valenti et al 1993). These facts may indicate that beyond a particular density, the social structure and behavior pattern is broken and, therefore, the effect within the population is no longer operative.…”
Section: Discussionsupporting
confidence: 51%
“…Increasing population density within the ponds also increases the level of intraspecific competition for vital resources, such as food and space. When one of these resources becomes insufficient, it becomes the limiting factor and the growth rate will decrease as a result of the lack of the resource and higher energy expenditure caused by the stress resulting from competition (Valenti et al 1993). In the present experiment, feed supplied was presumably abundant and proportional to prawn biomass in each pond.…”
Section: Discussionmentioning
confidence: 99%
“…Existem informações significativas sobre o crescimento de Decapoda de águas continentais, destacando-se os trabalhos com Palaemonidae (valenti et al, 1987, 1993, 1994Souza & fontoura, 1995;oH et al, 2002;Cartaxana, 2003) BondBuckup & Buckup, 1994noro & BuCkuP, 2003;silva-Castiglioni et al, 2006e Boss Jr. et al, 2006 O crescimento em comprimento de A. manuinflata foi analisado com base na distribuição de frequências absolutas em intervalos de classe de tamanho de 2 mm de CC, que corresponde à quarta parte do desvio padrão da média calculada para o total da amostra examinada (Markus, 1971). Os organismos com menos de três milímetros de comprimento não apresentavam pleópodos e os poros genitais eram difíceis de serem visualizados, o que impossibilitava uma sexagem segura; neste sentido, foram somados ao conjunto de ambos os sexos na análise da distribuição de frequência em classes de tamanho.…”
unclassified